The Highest German SS and Police Authorities in the Lithuanian General Region in 1941–1944 - Stankeras, Petras (Genocidas ir rezistencija, 2025)
The cadre policy of the Third Reich leader Adolph Hitler and his surrounding during the World War II with regard to occupied territories is not yet thoroughly investigated. The author, referring to the scarce historiographic data, published sources, memoirs, documents found in the Lithuanian Central archive, investigates and tries to elucidate the role of the SS and Police commandant institution in Lithuania. For the purpose the author, first, presents brief history of the SS and Police commandant institution in Germany and in Lithuania as well as biographies of four SS and Police commandants for the Lithuanian general region: Lucian Wysocki, Karl Schafer, Herman Harm, and Kurt Hintze. Besides, the competence and functions of their institutions on the territory of Lithuania are also examined. According to the Third Reich Officer index data, it has been estimated that during the years of war there had been established 2 superior SS and Police Commandant pasts; 37 Senior Commandant posts; and 43 SS and Police Commandant posts. Accordingly, the first position had been occupied by two SS Generals only: the second – by 99 Senior SS Officers; and the third one by 101 SS Officers. As the size of the territory belonging to the Third Reich changed, so did the number of posts of the SS and Police commandants. On the territory of Germany the position of the SS and Police commandant was not significant and bore a representative character. German SS and Police in Lithuanian general region were organized under the pattern of the Third Reich, except that it included Lithuanian police forces. Besides, those organs performed functions that were not characteristic for the police of the Third Reich. The service in SS and Police in Lithuania was equaled to the service in the East Front. The responsibilities of the SS and Police commandant in Lithuania were not completely defined. They had double subordination to the higher SS and Police commandant for Ostland and North Russia, and to the General Commissar of Lithuania Dr. Adrian Theodore Von Renteln. Lower in rank to Dr. A. T. Von Renteln was the SS and Police commandant, who was second in the official hierarchy in Lithuania, and actually executed the functions of the Minister of Police. Therefore, the SS and Police commandant had the right to issue obligatory orders and decrees, which, as a matter of fact, belonged to the competence of civil administration. Police governing bodies had actually formed an independent from civil administration, ruling system. The conflict between the civil administration of the Party and the SS and Police authorities demonstrated the short-sighted Nazi occupational policy, because execution of terror, colonization and maximum exploit of occupied territories was not possible without the SS and Police structures. The author concludes that the SS and Police commandants played an important role implementing the policy of the Third Reich and were the highest authority in an occupied territory. In Lithuania, in fact, all power was concentrated in their hands, as they were in charge of large military and police forces.